"My future is bright…I won't die with the cause of AIDS": ten‐year patient ART outcomes and experiences in South Africa. Issue 10 (14th October 2018) - Hendrickson, Cheryl J; Pascoe, Sophie J S; Huber, Amy N; Moolla, Aneesa; Maskew, Mhairi; Long, Lawrence C; Fox, Matthew P
Abstract: Introduction: South Africa is moving into a new era of HIV treatment with "treat all" policies where people may be on treatment for most of their lives. We need to understand treatment outcomes and facilitators of long‐term antiretroviral treatment (ART) adherence and retention‐in‐care in the South African context. In one of the first studies to investigate long‐term treatment outcomes in South Africa, we aimed to describe ten‐year patient outcomes at a large public‐sector HIV clinic in Johannesburg and explore patient experiences of the treatment programme over this time in order to ascertain factors that may aid or hinder long‐term adherence and retention. Methods: We conducted a cohort analysis (n = 6644) and in‐depth interviews (n = 24) among HIV‐positive adults initiating first‐line ART between April 2004 and March 2007. Using clinical records, we ascertained twelve‐month and ten‐year all‐cause mortality and loss to follow‐up (LTF). Cox proportional hazards regression was used to identify baseline predictors of attrition (mortality and LTF (>3 months late for the last scheduled visit)) at twelve months and ten years. Twenty‐four patients were purposively selected and interviewed to explore treatment programme experiences over ten years on ART. Results: Excluding transfers, 79.5% (95% confidence intervals (CI): 78.5 to 80.5) of the cohort were alive, in care at twelve months dropping to 35.1% (95% CI: 33.7 to 36.4) at ten years. Over 44% of deaths occurred within 12 months. Ten‐year all‐cause mortality increased, while LTF decreased slightly, with age. Year and age at ART initiation, sex, nationality, baseline CD4 count, anaemia, body mass index and initiating regimen were predictors of ten‐year attrition. Among patients interviewed, the pretreatment clinic environment, feelings of gratitude and good fortune, support networks, and self‐efficacy were facilitators of care; side effects, travel and worsening clinical conditions were barriers. Participants were generally optimistic about their futures and were committed to continued care. Conclusions: This study demonstrates the complexities of long‐term chronic HIV treatment with declining all‐cause mortality and increasing LTF over ten years. Barriers to long‐term retention still present a significant challenge. As more people become eligible for ART in South Africa under "treatment for all, " new healthcare delivery challenges will arise; interventions are needed to ensure long‐term programme successes continue.